Serum immune markers and disease progression in an incident Parkinson's disease cohort (ICICLE‐PD). Issue 7 (21st March 2016) - Williams‐Gray, Caroline H.; Wijeyekoon, Ruwani; Yarnall, Alison J.; Lawson, Rachael A.; Breen, David P.; Evans, Jonathan R.; Cummins, Gemma A.; Duncan, Gordon W.; Khoo, Tien K.; Burn, David J.; Barker, Roger A.; ,
ABSTRACT: Background: The immune system is a promising therapeutic target for disease modification in Parkinson's disease (PD), but appropriate immune‐related biomarkers must be identified to allow patient stratification for trials and tracking of therapeutic effects. The objective of this study was to investigate whether immune markers in peripheral blood are candidate prognostic biomarkers through determining their relationship with disease progression in PD. Methods: Serum samples were collected in incident PD cases and age‐matched controls. Subjects were clinically evaluated at baseline and 18 and 36 months. Ten cytokines and C‐reactive protein were measured, with data reduction using principal‐component analysis, and relationships between component scores and motor (MDS Unified Parkinson's Disease Rating Scale — part 3) and cognitive (Mini Mental State Examination [MMSE]) measures of disease severity/progression were investigated. Results: TNF‐α, IL1‐β, IL‐2, and IL‐10 were higher in PD (n = 230) than in controls (n = 93), P ≤ 0.001). Principal‐component analysis of log‐transformed data resulted in a 3‐component solution explaining 51% of the variance. Higher "proinflammatory" and lower "anti‐inflammatory" component scores were associated with more rapid motor progression over 36 months ( P < 0.05), and higher "proinflammatory" component scores were associated with lower MMSE at all times ( P < 0.05). Multiple linear regression analysis with adjustment for covariates confirmed "anti‐inflammatory" component score was the strongest predictor of slower motor progression (β = −0.22, P = 0.002), whereas proinflammatory cytokines were associated with lower baseline MMSE (β = −0.175, P = 0.007). Conclusions: Serum immune marker profile is predictive of disease progression in PD and hence a potential prognostic biomarker. However, interventional trials are needed to clarify whether peripheral immune changes causally contribute to the progression of PD. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society